Ayurvedic Approach In The Management of Pcos Related Secondary Infertility: A Case Study - Garg, Preeti; Sahu, Suman; Choudhary, Poonam; Bharathi, K (International Research Journal of Ayurveda & Yoga, 2021)
Failure to conceive by a couple of regular unprotected coitus within one or more years, defined as infertility. Primary infertility indicates those women who have never conceived. Secondary infertility denotes having previous pregnancy but failure to conceive subsequently. For conception fertility potential of the male and female partners are essential. For infertility, about 40-55 % of females are directly responsible, males about 30-40 %, both partners are responsible 10%, and rest 10% is unexplained. According to FIGO MANUAL (1990), ovulatory factors are 30-40% responsible for female infertility. Nowadays, PCOS (polycystic ovarian syndrome) is the day-to-day burning issue in the Stree and Prasuti OPDs and also become the most common cause of anovulation which further causes infertility. PCOS is affecting 20-30% of young reproductive age group women. Women with PCOS having irregular menstruation, excess of androgens, insulin resistance, anovulation, and infertility, etc. According to Ayurveda, these types of characters are found in Pushpaghni jataharini and Nasthartava (no proper follicle growth and anovulation). It involves dosha , dhatu, agni, and updhatu. A 21 years old female patient k/c/o PCOS, came to Stree roga and prasuti tantra OPD of NIA, Jaipur, with chief complaints of primary infertility since 1.5 years and scanty menses for 5 years. In this article, treatment with Stayanashodhak mahakashya gana kwath ,Madhumehari churna, and Phalasarpi is reported for 1.5 months and after that, she was conceived.